A Escola de Tempo Integral Raimundo Tomaz no Distrito de Tapera - Aquiraz: avaliação da política pedagógica do tempo integral e a repercussão na vida dos alunos - Almeida, Eronilda Cosmo de (2025)
The object of this study is to analyze the implementation of the Full-Time Education public policy at the Raimundo Tomaz High School, located in the district of Tapera, in the rural area of Aquiraz/CE. The research aims to evaluate the implementation of this policy in the school reality, considering the perceptions of the different subjects involved (managers, students, teachers and families) and the meanings perceived in the teaching-learning process, as well as in the students' permanence at school. The general aim of the research is to assess how the full-time public policy is implemented at the Raimundo Tomaz School in the district of Tapera-Aquiraz/CE. To this end, it is necessary to analyze the context in which educational policy is formulated at national and local level; to understand the nature of pedagogical actions, identifying the possible changes and difficulties arising from the application of the full-time education proposal in the lives of students, and, finally, to apprehend the challenges and possibilities of the full-time education policy in the municipality of Aquiraz, taking into account the perceptions of those interviewed. The methodology adopted is qualitative - without excluding quantitative and secondary data to grasp the object -, using the evaluation approach proposed by Rodrigues (2008; 2016), called